2021
DOI: 10.31004/cendekia.v5i3.803
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Self-Efficacy Terhadap Hasil Belajar Matematika

Abstract: Penelitian ini merupakan penelitian kuantitatif dengan metode survey yang bertujuan untuk mengetahui pengaruh self-efficacy siswa terhadap hasil belajar matematika. Data diperoleh dengan menggunakan instrumen self-efficacy berupa angket yang terdiri dari 20 pernyataan dengan skala likert. Populasi penelitian ini adalah seluruh siswa MTS DAAR EL-HUDA tahun pelajaran 2020/2021. Teknik pengambilan sampel adalah simple random sampling dimana sampel yang diambil sebanyak 30 orang. Uji statistik yang digunakan adala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 10 publications
0
4
0
6
Order By: Relevance
“…Similarly, studies by (Disai et al, 2017;Fitriani et al, 2021;Sari et al, 2021;Yunianti et al, 2016) found that students' learning outcomes in mathematics were positively correlated with their selfefficacy in completing related tasks. Conversely, students' learning outcomes in mathematics were negatively correlated with their self-efficacy in completing related tasks.…”
Section: Figure 1 Shows the St Topic Problem-solving Test's Answer Sheetmentioning
confidence: 90%
“…Similarly, studies by (Disai et al, 2017;Fitriani et al, 2021;Sari et al, 2021;Yunianti et al, 2016) found that students' learning outcomes in mathematics were positively correlated with their selfefficacy in completing related tasks. Conversely, students' learning outcomes in mathematics were negatively correlated with their self-efficacy in completing related tasks.…”
Section: Figure 1 Shows the St Topic Problem-solving Test's Answer Sheetmentioning
confidence: 90%
“…Development of website-based learning as an effort to utilize information technology so that nursing students increase interest, motivation to learn, and provide easy access learning module in nursing clinical practice (Nurfantri et al, 2022). To maximize learning during this pandemic, it is necessary to have high self-efficacy in students (Fitriani & Pujiastuti, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Banyak faktor yang mempengaruhi tingkat self efficacy seseorang (Fitriani & Pujiastuti, 2021), salah satu faktor tersebut menurut Bandura adalah faktor gender (Novena and Kriswandani 2018;Fadli 2020). Gender merupakan perbedaan perilaku, harapan, status dan peran antara pria dan wanita yang disebabkan oleh proses sosialisasi, penguatan, sosial budaya, agama, konstruksi dan bahkan melalui kekuasaan negara (Frendika et al, 2022).…”
Section: Pendahuluanunclassified